Processing of elicited information: good practices in requirements engineering - Hadad, Graciela Dora Susana (2024)
The elicitation of information in the requirements process is usually done through interviews. However, the practical indications about how to carry interviews out and how to use the elicited information when developing models do not prevent the appearance of some relevant systematic errors. Both in the literature and in the experiments carried out, it has been detected that the interviewer and/or the modeler usually introduce subjective information not obtained from the source of information, but from their previous knowledge. This distortion in the modeled information is usually transferred to other models and software artifacts and is detected too late. Therefore, an experiment was carried out that studied in detail how the information was obtained through an interview and how it was processed to build a model written in natural language. The use of incorrectly named concepts, non-existent concepts, poorly understood information, and vocabulary induced by the interviewer were detected in the model. Based on the distortions found in the modeled information, preliminary recommendations were made on how to conduct interviews and how to process the information for modeling, to mitigate cognitive biases of requirements engineers.